Benzothiazole-Containing Analogues of Triclocarban with Potent Antibacterial Activity - Catalano, Alessia (Antibiotics (Basel), 2021)
Triclocarban (TCC) is a polychlorinated, aromatic, antimicrobial agent commercially used since the 1950s in personal care products for the prevention of spoilage and infections. Humans are frequently exposed to TCC due to its widespread use, leading to its substantial release into the aquatic environment. With the recent ban of TCC from some personal care products, implemented in 2016, many replacement antimicrobial compounds have been studied by researchers. Herein, we report the synthesis and biological activity of a series of diarylureas, analogues of TCC that bear the benzothiazole nucleus as one of the two aryl moieties. Among the studied compounds, 2bF and 2eC showed the highest antimicrobial activity against Staphylococcus aureus, being also more active than TCC, with MIC values of 8 µg/mL versus 16 µg/mL of TCC. Moreover, compound 2bB was much more active than TCC against Enterococcus faecalis, a Gram-positive bacterium that is, unfortunately, strongly responsible for nosocomial infections. Finally, interesting results were found for compound 2bG that, even though less active than the others, exerts an interesting bactericidal action.